Complications Associated With Electromyography: A Systematic Review. (February 2020) - Cushman, Daniel M.; Strenn, Quinn; Elmer, Andrew; Yang, Aaron J.; Onofrei, Ligia
Abstract : Objectives: The aims of the study were to systematically review the available literature concerning complications due to electromyography and to review those associated with nerve conduction studies. Design: A systematic review was undertaken of Medline and Cochrane Central Register of Controlled Trials. Any complication related to clinical electromyography written in English was included, and all bibliographies were scanned for missed articles. Results: A total of 27 articles fit the inclusion criteria, with two observational studies, and the rest case series or case studies; 42 patients were reported. Of these, 28 patients required hospitalization and 22 required surgery or a procedure, with zero deaths reported. Needle-related complications were the most prevalent (18 patients reported), with 17 related to pneumothoraces. Disorders of hemostasis were identified in 13 patients (many were asymptomatic) and cutaneous disorders were identified in 11 patients. Only one complication was identified in the narrative review related to nerve conduction studies. Conclusions: This systematic review identified a variety of complications related to electromyography. Although the incidence of these occurrences cannot be elucidated from the case series and case study–predominant literature, adverse events seem to be rare but can cause significant morbidity. Electromyographers should be aware of all reported complications; this review outlines all reported occurrences that fit the inclusion criteria. Abstract : Supplemental digital content is available in the text.